Three-Dimensional Numerical Modeling of a Pressurized Solid Oxide Fuel Cell for Electric Aircraft Propulsion Systems Using Kinetic Parameters Determined By Impedance Spectroscopy - Hironori Nakajima; Shuya Wada; Takumi Matsuda; Keiichi Okai; Takayuki Kojima (ECS Meeting Abstracts, 2025)
We focus on the design of a pressurized solid oxide fuel cell integrated into a hybrid electric power generation system with a gas turbine (GT) (jet engine), aimed at propelling electric aircraft1)2). Compared to conventional aircraft, distributed propulsion with electric motors is expected to enhance the propulsion system efficiency. We have thus developed a three-dimensional numerical model of a planar SOFC pressurized for the combination with a GT for the optimal design and operation of practical cells and stacks3). A software package with the finite element method (COMSOL Multiphysics) is employed to analyze the current and temperature distributions in a cell. Exchange current densities for the anode and cathode under pressurized conditions are experimentally evaluated using an electrolyte-supported (YSZ) symmetrical tubular test cell for the electrochemical kinetics in the model by using impedance spectroscopy. Acknowledgments Thanks are offered to Professor Kohei Ito and Associate Professor Tatsumi Kitahara of Kyushu University for their valuable discussions. References 1) T. Kojima, K. Okai, T. Tagashira, Y. Fukuyama, Experimental Study on SOFC/GT Hybrid Engine for Liquid Hydrogen Fueled Electric Propulsion System, in: AIAA Aviat. 2023 Forum, American Institute of Aeronautics and Astronautics, Reston, Virginia, 2023. https://doi.org/10.2514/6.2023-3989. 2) K. Okai, T. Himeno, T. Watanabe, H. Nomura, T. Tagashira, A. Nishizawa, Potential of Aircraft Electric Propulsion with SOFC/GT Hybrid Core, in: 52nd AIAA/SAE/ASEE Jt. Propuls. Conf., American Institute of Aeronautics and Astronautics, Reston, Virginia, 2016. https://doi.org/10.2514/6.2016-4713. 3) H. Nakajima, J. Yamashita, K. Okai, T. Kojima, Numerical Modeling of a Pressurized Solid Oxide Fuel Cell for Electric Aircraft, ECS Meeting Abstract MA2023-01 (2023) 2726–2726. https://doi.org/10.1149/MA2023-01562726mtgabs.